Truncated separation method for characterizing and reconstructing bi-Gaussian stratified surfaces - Songtao Hu; Weifeng Huang; Noel Brunetiere; Xiangfeng Liu; Yuming Wang (Friction, 2017)
Abstract Existing ISO segmented and continuous separation methods for differentiating the two components contained within a bi-Gaussian stratified surface were developed based on the fit of the probability material ratio curve. In the present study, because of the significant effect of the plateau component on tribological behavior such as asperity contact, wear and friction, a truncated separation method is proposed based on the truncation of the upper Gaussian component defined by zero skewness. The three separation methods are applied to real worn surfaces. Surface-separation and surface-reconstruction results show that the truncated method accurately captures the upper component identically to the ISO and continuous ones. The identification of the lower component characteristics requires performing a curve fit procedure on the data left after truncation. However, the truncated method fails in identifying the upper component when the material ratio of the transition is less than 9%.